If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4)(8x + 2) = 0 Reorder the terms: (-4 + 3x)(8x + 2) = 0 Reorder the terms: (-4 + 3x)(2 + 8x) = 0 Multiply (-4 + 3x) * (2 + 8x) (-4(2 + 8x) + 3x * (2 + 8x)) = 0 ((2 * -4 + 8x * -4) + 3x * (2 + 8x)) = 0 ((-8 + -32x) + 3x * (2 + 8x)) = 0 (-8 + -32x + (2 * 3x + 8x * 3x)) = 0 (-8 + -32x + (6x + 24x2)) = 0 Combine like terms: -32x + 6x = -26x (-8 + -26x + 24x2) = 0 Solving -8 + -26x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + -13x + 12x2) = 0 Factor a trinomial. 2((-1 + -4x)(4 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-0.25, 1.333333333}
| 7a+4b-3a-b= | | 8+5n=-2 | | -3W=24 | | 9x=2x+44 | | 0.02+7=0.03x+5 | | Y=4(22-4)3(6)+6 | | 3(5x+2)-7(x+1)=71 | | 0.87500000x=0.77777778 | | 97-2541-23=k | | 8=0.66666666667x | | 37-918-11=d | | -0.6x=-24 | | 9=5m-2 | | 5x-5=x | | 88x-14=88x-15 | | 33+4y-5=14y-12-2y | | 4n-3=7n+6 | | 0.2z=-30 | | 4/5x+3/5=3 | | 10.25n=24 | | 3x^2-2y^2+2x-3y+5=0 | | -(5x-10)+4(5x+4)= | | (-9a^3b)(7ab^3)=0 | | 6x^2-13x-6= | | 1-3.4x=2.6x | | 8x=2x-2 | | 5m+7=s+5m-1 | | 29-3x=5-7x | | n*0.05=220500 | | 3x+12=-42-6x | | 6+3x=-4+x | | 7(5+m)=21 |